2009
DOI: 10.1103/physreve.80.037201
|View full text |Cite
|
Sign up to set email alerts
|

Spreading for the generalized nonlinear Schrödinger equation with disorder

Abstract: The dynamics of an initially localized wave packet is studied for the generalized nonlinear Schrödinger equation with a random potential, where the nonlinear term is beta|psi|ppsi and p is arbitrary. Mainly short times for which the numerical calculations can be performed accurately are considered. Long time calculations are presented as well. In particular, the subdiffusive behavior where the average second moment of the wave packet is of the form m2 approximately t(alpha) is computed. Contrary to former heur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 20 publications
6
48
0
Order By: Relevance
“…Understanding the effect of nonlinearity on the localization properties of wave packets in disordered systems has attracted the attention of many researchers to date. 9,11,13,14,[19][20][21][22][23][24][25][26][27][28] Most of these studies consider the evolution of an initially localized wave packet and show that it spreads subdiffusively for moderate nonlinearities, while for strong enough nonlinearities a substantial part of it is self-trapped. In such works, one typically analyzes normalized norm or energy distributions z l E l = P N i¼1 E i !…”
Section: A the Disordered Quartic Klein-gordon Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the effect of nonlinearity on the localization properties of wave packets in disordered systems has attracted the attention of many researchers to date. 9,11,13,14,[19][20][21][22][23][24][25][26][27][28] Most of these studies consider the evolution of an initially localized wave packet and show that it spreads subdiffusively for moderate nonlinearities, while for strong enough nonlinearities a substantial part of it is self-trapped. In such works, one typically analyzes normalized norm or energy distributions z l E l = P N i¼1 E i !…”
Section: A the Disordered Quartic Klein-gordon Modelmentioning
confidence: 99%
“…In particular, for single-site excitations the wave packet's spreading leads to an increase of the second moment according to m 2 $ t 1=3 , both in the diffusive as well as the self-trapping case. 9,11,19,21 Currently, a greatly debatable problem is the long time behavior of wave packet spreading in disordered nonlinear lattices. Recently, it was conjectured 15,16 that chaotically spreading wave packets will asymptotically approach KAM torus-like structures in phase-space, while numerical simulations typically do not show any sign of slowing down of the spreading behavior.…”
Section: A the Disordered Quartic Klein-gordon Modelmentioning
confidence: 99%
“…in different lattice models [8]. The interplay of these two localization mechanisms, nonlinearity and disorder, has been studied extensively in the recent years [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. In most of these studies, an initially localized wavepacket was shown to lead to delocalization and a sub-diffusive spreading of the energy, for sufficiently large nonlinearities.…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect of our system is the interplay between disorder and nonlinearity, which has been studied extensively in recent years [15][16][17][18][19][20][21][22][23][24][25][26][27][28], [29,Sec. 7.4].…”
mentioning
confidence: 99%